A REVISION OF ISEILEMA (GRAMINEAE) IN MALESIA - VELDKAMP, J. F. (Research Center for Biology, 2016)
VELDKAMP, J. F. 2016. A revision of Iseilema (Gramineae) in Malesia. Reinwardtia 15(2): 123 â 127. â There are three very rare and localized species in Malesia; one from Java is new. Notes on some other Southeast Asian species are given.